2019
DOI: 10.1007/s00223-019-00549-6
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ADAM12 in Chondrocyte Differentiation by Regulation of TGF-β1–Induced IGF-1 and RUNX-2 Expressions

Abstract: A disintegrin and metalloproteinase 12 (ADAM12) is known to be involved in chondrocyte proliferation and maturation however the mechanisms are not fully understood. In this study expression and localization of ADAM12 during chondrocyte differentiation was examined in the mouse growth plate by immunohistochemistry. Adam12 expression during ATDC5 chondrogenic differentiation was examined by real-time PCR and compared with the expression pattern of type X collagen. The clustered regularly interspaced short palind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Edem3, another candidate gene at the locus on chromosome 1 linked to body weight in early development (Supplemental Figure S5A), has previously been linked to short stature in humans based on family-based exome sequencing and differential expression in chondrocytes [44,]. Possibly sharing a similar mechanism, Adam12, a candidate gene in both a diet-independent and diet-dependent locus on chromosome 7, is known to play an important role in the differentiation, proliferation, and maturation of chondrocytes [45,].…”
Section: Resultsmentioning
confidence: 99%
“…Edem3, another candidate gene at the locus on chromosome 1 linked to body weight in early development (Supplemental Figure S5A), has previously been linked to short stature in humans based on family-based exome sequencing and differential expression in chondrocytes [44,]. Possibly sharing a similar mechanism, Adam12, a candidate gene in both a diet-independent and diet-dependent locus on chromosome 7, is known to play an important role in the differentiation, proliferation, and maturation of chondrocytes [45,].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the downregulation of ADAM12 could inhibit TGF-β1-induced cell proliferation in various cells types including human OA chondrocytes, murine stomal cells, and mouse pituitary adenoma cells [ 19 , 30 , 31 ]. In addition, a recent study indicated that ADAM12 overexpression can stimulate IGF-1 expression which is a major mitogen [ 32 ]. These data suggest that ADAM12 may mediate the pro-proliferation actions of TGF-β1.…”
Section: Resultsmentioning
confidence: 99%
“…ADAM12 was upregulated prior to Col10a1 during chondrogenic differentiation in ATDC5 cells. In addition, TGF-β1–induced ADAM12 overexpression resulted in upregulation of Igf-1 and downregulation of Runx2 expression ( Horita et al, 2019 ). The protein RUNX2 is a crucial transcription factor for type X collagen expression and chondrocyte hypertrophy and is known to regulate endochondral ossification through the control of chondrocyte proliferation and differentiation ( Chen et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%